Pengukuran Kualitas Citra Menggunakan Aplikasi ImageJ pada Gambaran Vertebra Lumbosacral dengan Proyeksi Lateral Posisi Supine Kasus Low Back Pain (LBP) - Aristia Wianing Putri (Jurnal Imejing Diagnostik (JImeD), 2023)
Background: This study aims to determine the measurement parameters of the imageJ software which can assess the quality of radiographic imae on clinical lumbosacral vertebra examination LBP by using a sample of radiographic image that has been obtained. This research conducted from March to April 2022 at STIKES An Nasher Cirebon.Methods: Study this method uses of pixel values obtained by the device imageJ software on images without any treatment, smoothing, sharpening, and brightness.Result: With the result obtained in smooth treatment did not differ when compared with no treatment an sufficient seen when compared with the sharpen treatment, in the enhance treatment 0%, 0.3%, 0.5%, and 1.0%, the higher the enhance value range, the bigger the pixel value and there is no overlap between the enhance values of 0%, 0.3%, 0.5%, and 1.0%, and at brightness treatment differences in brightnesss I is not much different from brightness III, except for brightness I and II, the difference is clearly visible in the graphic values.Conclusions: In this study it was found that the results of radiographic image that were treated with smoot, sharpen, enhance, and brightness with no treatment smoot, sharpen, enhance, and better brightness of radiographic image results with smoot, sharpen, enhance, and brightness and can establish a clearer diagnosis.